2014
DOI: 10.1080/00380768.2014.967167
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of CO2, N2O and CH4by222Rn and chamber methods in cold-temperate grassland soil, northern Japan

Abstract: This study conducted flux measurements of carbon dioxide (CO 2 ), nitrous oxide (N 2 O) and methane (CH 4 Rn method were in good agreement with those of the static chamber method, within the observed range of error, suggesting a high correlation coefficient of > 89% between the methods. Also, the temperatures of air and soil at 5-cm depth played a significant role in determining the fluxes of CO 2 and CH 4 measured by the 222 Rn and chamber methods; meanwhile, the N 2 O flux displayed an inverse exponential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Our study found opposing net fluxes of methane when comparing chamber fluxes (2010 and 2011) with eddy covariance methane fluxes. Published studies carried out to investigate grassland methane emissions with chambers mostly show a net uptake of methane (Beyer et al, 2015;Chiavegato et al, 2015;Kim and Tanaka, 2015;Wei et al, 2015), while eddy covariance based studies often show a net release of methane (Baldocchi et al, 2012;Dengel et al, 2011;Hörtnagl et al, 2018;Kroon et al, 2010). We identified three primary reasons for this discrepancy: (1) the difference in spatial scales that the individual methods investigate;…”
Section: Technical and Methodological Aspectsmentioning
confidence: 91%
“…Our study found opposing net fluxes of methane when comparing chamber fluxes (2010 and 2011) with eddy covariance methane fluxes. Published studies carried out to investigate grassland methane emissions with chambers mostly show a net uptake of methane (Beyer et al, 2015;Chiavegato et al, 2015;Kim and Tanaka, 2015;Wei et al, 2015), while eddy covariance based studies often show a net release of methane (Baldocchi et al, 2012;Dengel et al, 2011;Hörtnagl et al, 2018;Kroon et al, 2010). We identified three primary reasons for this discrepancy: (1) the difference in spatial scales that the individual methods investigate;…”
Section: Technical and Methodological Aspectsmentioning
confidence: 91%